Dual Pathway Inhibition with Low-Dose Direct Factor Xa Inhibition after Acute Coronary Syndromes—Why Is It Not Used in Clinical Practice? - Zeymer, Uwe; Schrage, Benedikt; Westermann, Dirk (Thrombosis and Haemostasis, 2018)
The optimal anti-thrombotic therapy for secondary prevention after an acute coronary syndrome is still a matter of debate. While current guidelines recommend dual anti-platelet therapy with aspirin and a P2Y12 inhibitor over 12 months especially in patients with stent implantation, the value of prolonged anticoagulation is still controversial. In the ATLAS-TIMI 52 trial, a low-dose direct factor Xa inhibition with rivaroxaban compared with placebo reduced the combined primary endpoint of cardiovascular mortality, myocardial infraction and stroke with an increase in major bleeding complications. This article discusses the value and problems of adding low-dose rivaroxaban to anti-platelet therapy as secondary prevention measure after an acute myocardial infarction. It will describe the pros and cons of intensified anti-platelet therapy versus dual pathway inhibition and give recommendations for different patient groups in clinical practice.
Keywords: acute myocardial infarction; anti-platelet agents; clinical trials; oral anticoagulants